1981
DOI: 10.1121/1.387124
|View full text |Cite
|
Sign up to set email alerts
|

Plasma angiotensin II changes with noise exposure at three levels of ambient temperature

Abstract: Significant plasma elevations of the powerful vasoconstrictor angiotensin II (AII) were measured in rats following exposure to either 100-dB or 20-dB SPL white noise in three environmental temperatures (5 degrees 21 degrees, and 38 degrees C). Loud noise exposure in the normal temperature condition (21 degrees C) and both temperature extremes with soft noise exposure resulted in plasma AII elevations. The two extreme temperatures combined with loud noise exposure resulted in plasma AII concentrations not diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1983
1983
1997
1997

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Therefore, the no-noise control group of the present study revealed somewhat elevated AI1 levels probably due to the stress of immobilization. Noise exposure (100 dB for 15 min) has previously been shown to elevate plasma AI1 concentration to a mean of about 0.64 ng/ml in rats [33], thus the present mean level of 1.08 ng following 30 min of noise exposure at 120 dB is in keeping with expected values.…”
Section: Noise Exposure and Aiisupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, the no-noise control group of the present study revealed somewhat elevated AI1 levels probably due to the stress of immobilization. Noise exposure (100 dB for 15 min) has previously been shown to elevate plasma AI1 concentration to a mean of about 0.64 ng/ml in rats [33], thus the present mean level of 1.08 ng following 30 min of noise exposure at 120 dB is in keeping with expected values.…”
Section: Noise Exposure and Aiisupporting
confidence: 87%
“…How-ever, this technique yields an indirect measure of blood flow and assumes, without confirmation, that external vessel caliber is proportional to flow. Our laboratory has measured significant elevations in circulating levels of AI1 in rodent and human subjects following exposure to loud noise [6,33]. Increases in plasma AI1 resulting from such exposure may thus modify cochlear blood flow either indirectly by shunting blood away from the peripheral vascdature or by acting directly upon the cochlear vasculature.…”
Section: Researchmentioning
confidence: 99%
“…
Previous investigations in our laboratory have measured significant increases in the circulating levels of the potent vasoconstrictive hormone, angiotensin II (AII; 26 and 64 pg/lOO pl plasma, normal and noise exposed, respectively), during and following noise exposure in the alert rat (Wright et al, 1981). In the present study, these levels were approximated through intra-arterial infusion in the anesthetized spontaneously hypertensive rat (SHR) and normotensive Wistar-Kyoto (WKY) rat.
…”
mentioning
confidence: 81%
“…It has. been shown that during intense noise exposure circulating AI1 levels are increased in humans (Dengerink et al, 1982) and normotensive rats (Wright et al, 1981). These elevations were sufficient to increase systemic blood pressure and lead to an increased CBF when approximated by exogenous infusion independent of noise (Wright et al, 1981).…”
Section: Introductionmentioning
confidence: 98%
“…Noise exposure, to which the subjects are not accustomed represents a higher degree of stress and stimulates the adrenal glands, which leads to augmented levels of epinephrine. The effects of noise on dopamine, growth hormone or plasma angiotensin II as indicators of sympathetic activity did not yield reliable results, probably due to wide distribution or difficulties in measuring (ANDREN 1982b;CESANA 1982b;BRANDENBERGER et al 1980;WRIGHT 1981).…”
Section: Biochemical Effects Of Noisementioning
confidence: 99%